An experimental investigation of slat-screens to mitigate fluid sloshing in microgravity. Issue 3 (September 2022) - Nadeem, Sobia; Bosca, Paula; Stramenga, Michael; Casella, Jonathan; Coppens, Jarod; Henriques, Josh; Wynn, Gabriella; Hamed, Mohamed
Abstract: The new age of space exploration has brought forth growing implications of space debris connected to satellites, and as such on-orbit satellite refuelling is an area of active research. To refuel a satellite on-orbit, a servicing satellite transfers propellant to the empty fuel tank of the satellite being serviced. A significant impediment to such a practice is the development of fluid sloshing motion during this process. This paper presents a study of the use of slat screens to damp fluid sloshing motion during a simulated refuelling of a fuel tank under microgravity conditions. There is particular interest in the sloshing motion developed due to internal forces produced from fluid injection. Two fluids, each analogous to common spacecraft propellants; hydrazine and liquid oxygen (LOX), were tested under a microgravity environment created by parabolic manoeuvres aboard the National Research Council of Canada's (NRC) Falcon 20 research aircraft. The experimental setup included three test chambers, two of which contained a perforated and a single-entry slat screen, designed to mitigate sloshing. High-speed imaging of fluid sloshing development within the test chambers was captured and analysed. The rate of fuelling was varied during subsequent parabolas to 25%, 50% and 75% of the internal volume capacity (1 L). Based on initial findings, statistical differences exist (P<0.05) in the latency for the LOX analogue, to reach 75% and 95% of the total chamber height. Differences were observed specifically between the control chamber and the chamber with perforated slat screens. Furthermore, qualitative observations of the hydrazine analogue fluid motion in microgravity show that at 50% fill ratio, slat screens result in a plateau of maximum fluid height. This suggests that slat screens may be an effective method of damping fluid sloshing motion and could be adopted by industry in the pursuit of on-orbit refuelling and the development of more sustainable spacecraft.